2022
DOI: 10.3390/jmse10020224
|View full text |Cite
|
Sign up to set email alerts
|

Site Selection of Offshore Solar Farm Deployment in the Aegean Sea, Greece

Abstract: Offshore solar energy presents a new opportunity for low-carbon energy transition. In this research, we identify and rank suitable Offshore Solar Farm (OSF) sites in the Aegean Sea, Greece, considering various constraints and assessment criteria. The methodology includes two distinct phases. In the first phase, Geographic Information Systems (GIS) are used to spatially depict both incompatible and compatible marine areas for OSF deployment, while in the second phase, two models based on different combinations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 56 publications
(72 reference statements)
0
8
0
Order By: Relevance
“…The methods used in different studies are presented in Table A1 of the Appendix. They include Analytic Hierarchy Process (AHP), Fuzzy Analytical Hierarchy Method (FAHP), Fuzzy‐Boolean logic, Analytical Network Process (ANP), Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS), Preference Ranking Organisation Method for Enrichment of Evaluations (PROMETHEE), Elimination, Choice Translating Reality (ELECTRE), Entropy Weighted Method (EWM), Best Worst Model (BWM), Step‐wise Weight Assessment Ratio Analysis (SWARA), Ordered Weighted Averaging (OWA) and Optimal Site Definition Model (ODM) [2, 4, 7–15].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The methods used in different studies are presented in Table A1 of the Appendix. They include Analytic Hierarchy Process (AHP), Fuzzy Analytical Hierarchy Method (FAHP), Fuzzy‐Boolean logic, Analytical Network Process (ANP), Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS), Preference Ranking Organisation Method for Enrichment of Evaluations (PROMETHEE), Elimination, Choice Translating Reality (ELECTRE), Entropy Weighted Method (EWM), Best Worst Model (BWM), Step‐wise Weight Assessment Ratio Analysis (SWARA), Ordered Weighted Averaging (OWA) and Optimal Site Definition Model (ODM) [2, 4, 7–15].…”
Section: Methodsmentioning
confidence: 99%
“…Multi-Criteria Decision-Making (MCDM) methods provide a structured and systematic approach to handle conflicting criteria and make informed decisions. The literature review identified 33 [2,4,[7][8][9][10][11][12][13][14][15].…”
Section: Multi-criteria Decision-making Methodsmentioning
confidence: 99%
“…In the sequence, a running case study is employed to highlight some of the issues involved. To avoid using proprietary information from Archirodon, and to alleviate possible concerns about a conveniently designed example, the case study is based on publicly available data for a specific problem of designing an offshore solar farm installation 26 . All data generated or analyzed during this study are included in the body of this paper.…”
Section: Mcda—the View From the Fieldmentioning
confidence: 99%
“…The case study involves the problem of site selection of an offshore solar farm deployment in the Aegean Sea, Greece 26 . There were nine candidate locations (MA1 ÷ MA9) and seven assessment criteria (AC1 ÷ AC7) as outlined in Table 1 .…”
Section: Offshore Wind Farm Installation—a Case Studymentioning
confidence: 99%
See 1 more Smart Citation